(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the geographical and ecological distribution of endemic plants in the Green Mountain region of northeastern Libya, identifying the natural and climatic factors influencing their spatial organization, and assessing their economic and environmental value. The Green Mountain region is one of the most plant-diverse areas in Libya, due to its varied topographical characteristics and climatic range, from Mediterranean in the north to arid and semi-arid environments in the south. This has contributed to the development of diverse plant habitats characterized by species diversity and density. The study employed a descriptive-analytical approach, utilizing field surveys and questionnaires administered to local residents, herbalists, and farmers, in addition to reviewing previous studies and relevant environmental reports. The study sample comprised 100 participants from the relevant groups, taking into account the geographical and ecological diversity of the study sites. The study employed descriptive, statistical, and economic analysis methods to interpret the data and assess the economic importance of the endemic plants. The results showed that Jabal Akhdar is home to a large number of endemic, aromatic, and medicinal plants used in various fields such as traditional medicine, traditional industries, essential oil production, and food, contributing significantly to the local economy. The findings also indicated a growing or stable demand for some of these plants, making them a sustainable source of income for a number of workers in this sector, despite challenges related to the scarcity of some species and the difficulty in obtaining them at certain times. The study concluded that the endemic plants of Jabal Akhdar represent a vital natural and economic resource, necessitating their scientific documentation and ecological classification, as well as the development of strategies for their sustainable use. This would achieve a balance between economic benefit and the preservation of biodiversity. The study also recommends raising environmental awareness among local residents and encouraging scientific research and sustainable investment in this natural resource to protect it from environmental threats such as overgrazing, unregulated urban expansion, and climate change, thus ensuring its continuity for future generations.